Attitudes towards the risks of climate change: Contributions from a Chilean exploratory case study - Natalia Romero; Barbara Orme\~no; Lisbeth Simón (The Central European Review of Economics and Management (CEREM), 2022)
Aim: The alteration of the planetary climate, mainly because of human activity, could trigger ecological, economic, and social impacts capable of disrupting the forms of life on the planet. In this context, the influence of psychosocial factors on the environmental awareness and the way in which these factors can for support pro-environmental behaviors is researched on the example of students from a Chilean university. Design / Research methods: Transactional exploratory mixed research. Bibliographic review and application of a survey to the community of a Chilean university (n=134). The process consisted mainly of two stages: (1) literature review and (2) survey application. Conclusions / Findings: The reviewed authors agree that people exhibit pro-environmental behaviors when they are sufficiently informed about environmental problems, have a favorable attitude towards them and can generate effective qualitative changes that do not cause significant difficulties later on. The results of the survey applied to the university sample show that the respondents can perceive the damage of global warming and have pro-environmental behaviors in greater proportion compared to the bibliographic data reviewed. The results are exploratory; however, they provide a focus for future research in this context. Originality / Value of the article: This article offers an updated perspective on perceptions in relation to climate change and pro-environmental behaviors, based on the case study. Additionally, it offers a proposal for the intervention of university educational plans.
Keywords: I23; Q01; O44; 330; global warming; pro-environmental behaviors; society; sustainability